PENGARUH MEDIA QUESTION CARD TERHADAP HASIL BELAJAR SISWA PADA MATERI SINONIM DAN ANTONIM KELAS V SD NEGERI LAMPEUNEURUT - Zahra Tunnisa; Aida Fitri; Hasniyati Hasniyati (STKIP Subang, 2026)
This study aims to determine the effect of question card media on student learning outcomes on synonym and antonym material for class V of Lampeuneurut State Elementary School. This study uses a quantitative approach. The type of research is an experiment with a quasi-experimental design. The population is all fifth-grade students of Lampeuneurut State Elementary School, Aceh Besar Regency, totaling 34 students. The research sample is class V A and V B, each consisting of 17 students. In the calculation of hypothesis testing carried out using a t-test based on a significance level of α = 0.05, the researcher obtained a significance result (2-tailed) of 0.025. Where 0.025 <0.05, so there is an effect of question card media on student learning outcomes on synonyms and antonyms material for class V of Lampeuneurut State Elementary School, Aceh Besar.